Caribbean Small States : Challenges of High Debt and Low Growth. (Policy Papers; Policy Paper ;, 2013)
This paper presents background on Caribbean small states as context for the main paper, 'Macroeconomic Issues in Small States and Implications for Fund Engagement.' It draws on recent analytical work presented at a conference for policy makers in September 2012, in Trinidad and Tobago. Caribbean small states, while sharing many features of other small states (size-related macroeconomic vulnerabilities, lack of economies of scale, and capacity constraints) have specific characteristics which merit attention.